Proses Rekruitmen Pimpinan Birokrasi Pemerintah Daerah di Kabupaten Sleman dan Kota Parepare - Zulchaidir Zulchaidir (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2011)
This article describes about the recruitment process of bureaucracy leader in Sleman region and Parepare city, Including several factors that influences the recruitment process.The methodology that implemented in this article is quantitative description with indepth interview and observation as the means on collecting the data. This articles found that the recruitment process of bureaucracy in Sleman district has implemented “competent testing system” in appointing goverment officials with also considering the role of Baperjakat, while Parepare city has not implemented the testing system yet. There is also several factors that influenced the recruitment process in Parepare which have been identified, which are: head of district commitments, personnels information, political interest and the role of academic institutions.